MS-150-10-f02-002: Letter from the Marquis de Maha Yo - Yo, Maha, Marquis de (Valdosta, GA: Valdosta State University Archives and Special Collections, 1896)
Letter from the Marquis de Maha Yo[tha] thanking him for Arnold’s note of farewell, November 6. On The Siamese Legation, stationary 23, Ashburn Place, London, S.W.
1 handwritten note on stationary, 1 page.
Keywords: Personal correspondence; Letters; Poets--Correspondence; Arnold, Edwin, Sir, 1832-1904